2000
DOI: 10.5860/crl.61.4.313
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Publisher Quality by Political Science Librarians

Abstract: Publisher quality is one criterion used by collection development librarians in making book selection decisions. Few studies have assessed the perceptions subject specialist librarians have about the quality of academic publishers’ output in specific disciplines. The author surveyed a sample of members of the Association of College and Research Libraries Law & Political Science Section, asking them to assess the overall quality of political science books published by sixty-two academic presses and imprints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…But it is hardly in dispute that authors want to publish with the best presses they can. We therefore see quality rankings as a justifiable means of testing libcitation validity, and we would expect rankings of academic publishers (as in Lewis 2000) to covary significantly with libcitation counts of books.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But it is hardly in dispute that authors want to publish with the best presses they can. We therefore see quality rankings as a justifiable means of testing libcitation validity, and we would expect rankings of academic publishers (as in Lewis 2000) to covary significantly with libcitation counts of books.…”
Section: Discussionmentioning
confidence: 99%
“…Libcitations should also correlate with quality rankings of the presses that publish academic books (Metz & Stemmer 1996;Goodson et al 1999;Lewis 2000;Wiberley 2002Wiberley , 2004. Similar quality rankings of academic journals (East 2006;Mingers & Harzing 2007;Haddow 2008) have proved controversial (see, e.g., Corbyn 2008a.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to determine the quality of publishers in certain disciplines, particularly political science (Garand & Giles, 2011;Goodson, Dillman & Hira, 1999;Lewis, 2000), economics (Laband, 1990;Torres-Salinas & Moed, 2009), and criminology (Gabbidon, Higgins & Martin, 2010). These studies have employed various methods including surveys and the creation of new metrics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors found that the rankings were quite consistent regardless of institution type or collection development experience. Lewis (2000) applied a method originally used in a survey of political scientists (Goodson, Dillman, & Hira, 1999) to examine the preferences of librarians who specialize in the development and management of political science collections. These two studies provide an opportunity to compare the opinions of practicing academicians toward subject-specialist librarians.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Publisher "quality" has previously been assessed using survey studies (Garand & Giles, 2011;Goodson, Dillman, & Hira, 1999;Lewis, 2000;Metz & Stemmer, 1996) and has also been related to library catalogue holdings (Donovan & Butler, 2007; SENSE-Research School for Socio-Economic and Natural Sciences of the Environment, 2009) and number of reviews per publisher and publisher reputation (Jordy, McGrath, & Rutledge, 1999). The concept of prestige, which is slightly different from "quality," is often associated with academic publishing advice, specifically the the selection of a university press by a scholar who has written a new book (Pasco, 2002;Pratt, 1993;Rowson, 1995).…”
Section: Introductionmentioning
confidence: 99%